2018
DOI: 10.1264/jsme2.me17170
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence Network Reveals the Higher Fragmentation of the Bacterial Community in Kaidu River Than Its Tributaries in Northwestern China

Abstract: Rivers and their tributaries sculpt the earth’s surface, and play an important role in substance circulation and energy flow. Bacteria are involved in most biogeochemical processes in the fluvial ecosystem; however, their pattern distribution in a river and its tributaries has not yet been investigated in detail. In the present study, high-throughput sequencing was employed to examine bacterial communities and their co-occurrence networks between Kaidu River and its nine tributaries in northwestern China. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 92 publications
3
17
0
Order By: Relevance
“…Within melt ponds and periglacial rivers, network inference indicated that positive correlations prevailed in the bacterial communities. This correlative pattern is in line with that reported from other habitats, including soil [62], rivers [60], and other glacial environments [26,27]. As previously suggested [37], positive association in a network is interpreted as cross-feeding, co-colonization, and co-aggregation.…”
Section: Higher Competitive and Connected Network Of Bacterial Communsupporting
confidence: 91%
See 1 more Smart Citation
“…Within melt ponds and periglacial rivers, network inference indicated that positive correlations prevailed in the bacterial communities. This correlative pattern is in line with that reported from other habitats, including soil [62], rivers [60], and other glacial environments [26,27]. As previously suggested [37], positive association in a network is interpreted as cross-feeding, co-colonization, and co-aggregation.…”
Section: Higher Competitive and Connected Network Of Bacterial Communsupporting
confidence: 91%
“…In our present study, co-occurrence networks in melt ponds and periglacial rivers suggested that most of the involved nodes belonged to the rare sub-communities. This pattern has previously been reported from other glacial environments in Tibet Plateau [23] and from other habitats, such as soil [58,59], rivers [60], and oceans [61]. Moreover, the over-proportional roles of rare taxa were also shown by our finding that all 7 keystones in melt ponds and 11 out of 12 keystones in periglacial rivers were affiliated with rare OTUs.…”
Section: The Role Of Rare Sub-communities On the Bacterial Communitiesupporting
confidence: 90%
“…This suggested that the other genera respond more strongly to the metabolites produced by these five genera [62]. At the same time, because these bacterial taxa have highly connected nodes, they are recognized as keystone taxa here [14,63]. Compared with other taxa in the network, keystone taxa play an important role in maintaining the network structure [22].…”
Section: Discussionmentioning
confidence: 99%
“…Inland lakes are often separated by land, and even when they are connected by rivers, there are hydrodynamic gradients. The environmental conditions and diversity of microbial communities in these habitats often have significant spatial heterogeneity (13,17,(21)(22)(23)(24). Abundant and rare bacteria differ significantly in their biodiversities (6) and may have discrepant ecological niches and different ecological responses to environmental changes (6,13,20).…”
mentioning
confidence: 99%